APLIKASI DATA LANDSAT DAN SIG UNTUK POTENSI LAHAN TAMBAK DI KABUPATEN BANYUWANGI - Parwati, Ety; Carolita, Ita; Effendy, Iskandar (Institut Teknologi Sepuluh Nopember, 2004)
The application of Remote Sensing and Geographic Information System are used to evaluate land potential that is suitable for cultivation of fishpond. The parameter that is used in this research is the existing land use by remote sensing and analysis process, topographic/land slope,kind of land, climate data (such as; rainfall and amount of dry season). The evaluation of land potential gives 4 land suitability levels, they are 1)Suitable level:2)Rather suitable level:3)Less suitable level and:4)Non suitable level. The analysis shows that are three areas in Banyuwangi sub-province that is suitable for fishpond cultivation: they are Muncar, Rogojampi, and Pesanggrahan districts.